Pengentasan Kemiskinan Di Kalimantan Tengah - Tiur Roida Simbolon; Elja Erwita Sinaga; Puput Iswandyah Raysharie; Alexandra Hukom; Dedi Takari (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this research is to ascertain whether public consumption (RT), TPT, and income affect the poverty rate in Central Kalimantan between 2013 and 2022. Poverty is one of the problems that has always been the main concern of the community. Even though individuals who are touched by the issue of poverty are often unaware of it, it can have an impact on various aspects of human life (Pdrb et al., 2018). Unemployment is a condition where a person is actively looking for a job but has not got one. Monthly costs of food and non-food consumption Per capita expenditure is calculated as the total number of household members divided by the total number of household members. These results provide a comprehensive analysis by describing data (results), previous work or theory and testing multicollinearity, autocorrelation, heteroscedasticity, normality. To explain the results of multiple linear regression analysis based on traditional assumption tests, T-tests, F-tests, and coefficient tests are used. determination. The results of this study indicate that public consumption and unemployment do not have a significant impact on poverty. Meanwhile, the relationship between per capita expenditure has a significant influence on poverty.